Dietary assessment, nutrition knowledge, and pregnancy outcome in high-risk pregnant Korean women - Min Jung Kim; Hee-Sook Lim; Hae-Hyeog Lee; Tae-Hee Kim; Yongsoon Park (IMR Press, 2021)
Background: The nutritional status of pregnant women has a significant impact on maternal health, fetal growth, and pregnancy outcomes. The purpose of this study was to investigate the associations among advanced maternal age, eating habits, knowledge level, and obstetric outcome in pregnant women. Methods: We conducted an observational single center study of 168 pregnant women. The participants were divided into three groups by age: group I (≤29 years old, n = 36), group II (30 to 34 years old, n = 87), and group III (≥35 years old, n = 45). We studied general features, dietary habits, nutritional knowledge and necessity of education, and understanding of dietary guidelines and practice of them. Results: The pre-pregnancy weight of pregnant women significantly increased with age (p = 0.002), and the group I pregnant women were more likely to be underweight, while rates of overweight and obesity were higher in the group III women than the other groups (p < 0.001). Frequencies of hypertension and gestational diabetes tended to increase as the age of mother increased. In the assessment of level of knowledge of information about pregnancy, childbearing, and infant care, pregnant women who responded "do not know at all or do not know" was higher in group I than group III (p = 0.025). During pregnancy, the experience of having received counseling or education was less common in group I compared to the other groups, but the difference was not statistically significant. The total score for dietary action guidelines was lower in group I, but the difference was not statistically significant. Conclusion: The pregnancy outcome will be good, despite advanced maternal age, if they have good nutritional status, a healthy lifestyle, good and knowledge of nutrition.